Empowering Elementary School Children Through Yoga Pranayama Exercises: An Effort to Improve Emotion Regulation - Luh Putu Widiastini; I Gusti Agung Manik Karuniadi; Ni Made Egar Adhiestiani (Universitas STRADA Indonesia, 2026)
Adolescence is a transitional period between childhood and adulthood, marked by significant biological, psychological, and socio-cultural changes. One of the common issues during this stage is the inability to manage emotions effectively, which can increase the risk of mental disorders such as depression. Interviews with the principal and homeroom teacher at SDN 5 Dalung revealed that fourth- and fifth-grade students. engage in fights or bullying almost every day, reflecting low emotional regulation skills. One intervention that can be implemented is complementary therapy in the form of pranayama yoga. Pranayama yoga is a breathing technique that stimulates the release of endorphins, provides a calming effect, lowers blood pressure, and improves emotional stability. This community service activity was carried out on April 10-11, 2025, and involved 50 fourth- and fifth-grade students. Evaluation was conducted using the DERS-SF instrument (18 items) before and after the intervention. The results showed that before the intervention, 96% of students were in the high emotional regulation difficulty category. After the intervention, this percentage decreased to 66%, with 34% moving into the moderate category. The average DERS score also dropped significantly from 75.08 to 64.72, with a t-test result of t = 6.698 and p = 0.001, which is statistically significant. In conclusion, pranayama yoga has been proven effective in improving emotional regulation among elementary school students and can be used as a simple, safe, and applicable complementary approach to support mental health in schools.